Royal Flying Doctor Service. Season 2 [videorecording (DVD)] - Meadows, Ian, 1983-; Banks, Imogen; Fennessy, Mark (PBS Distribution, 2024)
In Australia's red heart with all of its precarious beauty, the modern-day heroes of the Royal Flying Doctor Service navigate private lives as turbulent and profound as the heart-stopping emergencies they attend.